PENGARUH PARAMETER PROSES TERHADAP DIMENSI CASING GEAR DENGAN PRODUKSI MENGGUNAKAN TEKNOLOGI 3D PRINTER DLP (DIGITAL LIGHT PROCESS) - Dicky Seprianto; Ahmad Zamheri; Almadora Anwar Sani; Nanda Yusril Mahendra (Jurnal Poli-Teknologi, 2021)
DLP (Digital Light Process) 3D Printer Technology is a 3 dimensional printing machine made from resin with a lighting system using a light projector with a layer-by-layer printing process. In this research, the writer will make an object, which is one of the machining components, namely the gearbox casing. In this study the authors will analyze the effect of process parameters (exposure time, off time, and their interaction) on the dimensions of the printout and get the most optimal parameters to be applied to components or printing objects. In conducting testing, the measurement of the tester’s dimensions uses the Krisbow KW06-422 calipers. Then the measurement data is processed by the Anova method with the help of software design expert version 10. After the research process obtained the results that the most influential parameters are the interaction factor between exposure time parameters and off time parameters on the dimensions of the printed objects, and the most optimal combination of parameters is found in the exposure time parameters 10 second and off time 1 second with a level of precision of 95%.